'Frail but Fearless': Dichotomies of femininity and strength at the New York Hippodrome, 1905–17. Issue 2 (1st December 2019) - Merriman, Rebecca
This article examines two women who performed athletic feats at the New York Hippodrome between 1905 and 1917, arguing that their approaches to costume and bodily display were integral to their widespread critical and public acclaim. The women examined are lion tamer Claire Heliot and swimmer and diver Annette Kellerman. I contend that these performers occupied a difficult position within the early-twentieth-century entertainment industry. The type of mainstream spectacle that the Hippodrome provided, combined with strict societal ideas of what constituted femininity and masculinity, created an environment that was not conducive to the success of athletic women.Their unusual acts therefore required them to negotiate their public image in such a way that emphasized their inherent femininity. Their costume was an essential element of this negotiation as it exposed the audience to a kind of woman with whom they were already familiar. Claire Heliot did this by occupying a traditional domestic womanhood that sharply contrasted with her dangerous lion-taming act, and Annette Kellerman emphasized her beauty through the sexually charged display of her body in form-fitting costumes and swimsuits. In addition to analyses of their costumes, critical responses to their performances are taken into consideration as evidence of these women's success as performers. This article highlights how costume and the body can be used as tools to alter identity and reinforce gender norms for the purposes of subverting the physical expectations of women.